2011
DOI: 10.1021/ol200252c
|View full text |Cite
|
Sign up to set email alerts
|

A Domino Process for Benzyne Preparation: Dual Activation of o-(Trimethylsilyl)phenols by Nonafluorobutanesulfonyl Fluoride

Abstract: Benzynes were generated from o-(trimethylsilyl)phenols using nonafluorobutanesulfonyl fluoride (NfF) by a domino process, i.e., the nonaflation of the phenolic hydroxyl group of o-(trimethylsilyl)phenols by NfF followed by the attack of the produced fluoride ion on the trimethylsilyl group. The generated benzyne immediately underwent various reactions to give polysubstituted benzenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 23 publications
(17 reference statements)
1
34
0
Order By: Relevance
“…Among the various solvents examined, tetrahydrofuran and 1,2-dimethoxyethane gave the best results (entries 5-9). Conversely, generation of benzyne was not observed when cesium carbonate was replaced by cesium bicarbonate (entry 10), which was previously used concomitantly with cesium carbonate and 18-crown-6 to generate benzyne from 2-(trimethylsilyl)phenyl nonaflate with moderate efficiency [38]. Moreover, the efficiency of the reaction was reduced when potassium carbonate and 18-crown-6, which can retain a potassium cation inside the molecule, were used (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various solvents examined, tetrahydrofuran and 1,2-dimethoxyethane gave the best results (entries 5-9). Conversely, generation of benzyne was not observed when cesium carbonate was replaced by cesium bicarbonate (entry 10), which was previously used concomitantly with cesium carbonate and 18-crown-6 to generate benzyne from 2-(trimethylsilyl)phenyl nonaflate with moderate efficiency [38]. Moreover, the efficiency of the reaction was reduced when potassium carbonate and 18-crown-6, which can retain a potassium cation inside the molecule, were used (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…15 Moreover, Akai and co-workers reported that ortho-silylaryl nonaflates could serve as aryne precursors, which were prepared in situ by treating orthosilylphenols with nonafluorobutanesulfonyl fluoride, cesium carbonate, and 18-crown-6 ether ( Figure 2D). 16 In addition, we recently developed a fluoride-free method using cesium carbonate and a crown ether to generate arynes from ortho-silylaryl triflates at room temperature ( Figure 2E). 17 Furthermore, we have recently developed a facile method to diversify the simple ortho-silylaryl triflates by utilizing an Ircatalyzed regioselective CH borylation reaction (Scheme 1).…”
Section: Precursors and Activatorsmentioning
confidence: 99%
“…( Table 1): Following general procedure B, a mixture of 4,5-dimethoxy-2-(trimethylsilyl)phenol (1a) [2] (0.50 g, 2.2 mmol), NaH (60% in mineral oil, 0.13 g, 3.3 mmol), 18-crown-6 (0.58 g, 2.2 mmol) and NfF (0.77 mL, 4.4 mmol) was stirred in THF (22 mL, 0.1 M) at 60 °C for 1 h. The titled compound 2a was obtained as a colorless oil (1.0 g, 91%). Rf: 0.2 (hexane/EtOAc = 5:1).…”
Section: 5-dimethoxy-2-(trimethylsilyl)phenyl 112233444-nonmentioning
confidence: 99%